2014
DOI: 10.5271/sjweh.3454
|View full text |Cite
|
Sign up to set email alerts
|

For better or worse? Changing shift schedules and the risk of work injury among men and women

Abstract: For better or worse? Changing shift schedules and the risk of work injury among men and women by Wong IS, Smith PM, Mustard CA, Gignac MAM There are currently no studies which examine the risk of work injury associated with changes in shift type; our study addresses this gap. Results suggest the need to implement occupational health and safety programs soon after changes in shift schedules. Results also highlight the importance of greater awareness of health and safety actions on an ongoing basis, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…In a study of shift work and metabolic syndrome, Puttonen et al (36) pointed out that, although the reasons for the observed gender differences are not completely known, the characteristics of the working conditions of men and women may influence the associations found. Gender differences across some industries, such as healthcare and manufacturing, may also result in different hazard exposures among men and women and influence the risk of work injury (35). Concerning the sociodemographic and behavioral aspects, gender differences were examined in this present study, but no results were observed to explain the differential odds of DM2 among men and women.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In a study of shift work and metabolic syndrome, Puttonen et al (36) pointed out that, although the reasons for the observed gender differences are not completely known, the characteristics of the working conditions of men and women may influence the associations found. Gender differences across some industries, such as healthcare and manufacturing, may also result in different hazard exposures among men and women and influence the risk of work injury (35). Concerning the sociodemographic and behavioral aspects, gender differences were examined in this present study, but no results were observed to explain the differential odds of DM2 among men and women.…”
Section: Discussionmentioning
confidence: 41%
“…Regarding gender differences, studies of diabetes (31), metabolic syndrome (32) and cardiovascular disease (33) point to possible different impacts by sex, while Wong et al (34,35) and Puttonen et al (36) have discussed aspects relating to work schedule. In a study of shift work and metabolic syndrome, Puttonen et al (36) pointed out that, although the reasons for the observed gender differences are not completely known, the characteristics of the working conditions of men and women may influence the associations found.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolation of these laboratory findings to the real world would suggest that women are more affected by night-shift work than men. Indeed, reports that have looked at sex differences in working hours, work shifts, and occupational injuries show that women seem to be at increased risk for occupational injuries during extended work shifts, nonstandard shifts, and changing shifts (61). This difference may in part reflect social factors such as family and childcare responsibilities that lead women to work longer hours and to sleep less on days off than men (62).…”
Section: Circadian and Time Awake-dependent Regulation Of Waking Funcmentioning
confidence: 99%
“…States associated with relative neurocognitive impairment, such as after significant alterations in the timing of shift work and after periods of significantly restricted sleep, have been demonstrated on multiple occasions to negatively impact motor performance and increased risk for task error and musculoskeletal injuries in these circumstances (1,39,47). Similar studies have been performed in athletes under conditions of sleep restriction.…”
Section: Neurocognitive Performance and Musculoskeletal Injury Riskmentioning
confidence: 99%